2004
DOI: 10.1007/s00125-003-1261-y
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of hepatic and intestinal Abcg5 and Abcg8 expression associated with altered sterol fluxes in rats with streptozotocin-induced diabetes

Abstract: Aim/hypothesis. Type I diabetes is associated with altered hepatic bile formation and increased intestinal cholesterol absorption. The aim of this study was to evaluate whether altered expression of the ATP-Binding Cassette half-transporters Abcg5 and Abcg8, recently implicated in control of both hepatobiliary cholesterol secretion and intestinal cholesterol absorption, contributes to changed cholesterol metabolism in experimental diabetes. Methods. mRNA and protein expression of Abcg5 and Abcg8 were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 48 publications
6
36
1
1
Order By: Relevance
“…It is interesting to see that polymorphisms in the Q604E allele of the ABCG5 gene in men were associated with insulin resistance [32]. In streptozotocin-induced diabetes in rats it has been shown that intestinal mRNA expression of ABCG5 and ABCG8 and ABCG5 protein content were reduced as was ABCG5 and ABCG8 expression in the liver [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to see that polymorphisms in the Q604E allele of the ABCG5 gene in men were associated with insulin resistance [32]. In streptozotocin-induced diabetes in rats it has been shown that intestinal mRNA expression of ABCG5 and ABCG8 and ABCG5 protein content were reduced as was ABCG5 and ABCG8 expression in the liver [33].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, overexpression of human ABCG5/G8 raised the gall bladder cholesterol concentrations by more than 5-fold and reduced dietary sterol absorption by 50% in transgenic mice (24). Finally, recent studies in mice and rats have demonstrated an association between ABCG5 and ABCG8 gene expression and changes in biliary cholesterol secretion and intestinal cholesterol absorption (25)(26)(27). Thus, ABCG5/G8 are transporters that play a major role in the excretion of cholesterol and other sterols from the body.…”
mentioning
confidence: 99%
“…Rats with induced diabetes have been shown to have impaired expression of ABCG5/G8 that was partially reversed with insulin treatment [100]. Similarly, this trend in impairment was found in Zucker diabetic rats [101] and in type 2 diabetic subjects [71].…”
Section: Pharmacological Targeting Of Intestinal Cholesterol Absorptionmentioning
confidence: 75%